Visualizing Samsonfish (Seriola hippos) with a Reson 7125 Seabat multibeam sonar - Parsons, Miles; Parnum, Iain; McCauley, Robert (Oxford University Press 2009, 2013)
In Western Australia, aggregations of Samsonfish (Seriola hippos) form each summer to spawn in waters west of Rottnest Island. In this study, a Reson 7125 Seabat multibeam sonar (400 kHz) was pole mounted aboard a 21.6 m vessel, conducting acoustic transects to acquire acoustic backscatter simultaneously from a midwater aggregation of S. hippos and the wreck it surrounded. The processedbackscatter produced high-resolution visualizations of both the fish and seabed. During a 15 min period, the centroid of the aggregation moved 91 m around the eastern and northeastern side of the wreck and probably exhibited lateral vessel avoidance behaviour from the survey vessel. Additionally, a ortheasterly current at the site was inferred from subtle habitat features, suggesting that at thetime of the survey the aggregation preferred to remain upcurrent of the wreck. These findings confirmed that the S. hippos aggregations do not necessarily remain directly above the wrecks and do not always remain sedentary. Aggregation acoustic density packing at the survey site was observed at 12.7+2.4 m3 per fish, equivalent to 1.6+0.1 body lengths nearest-neighbour distance.